2013
DOI: 10.1007/s00228-013-1502-z
|View full text |Cite
|
Sign up to set email alerts
|

Dose adjustment in patients with liver cirrhosis: impact on adverse drug reactions and hospitalizations

Abstract: Aim and background To assess drug-related problems in patients with liver cirrhosis by investigating the prevalence of inadequately dosed drugs and their association with adverse drug reactions (ADRs) and hospitalizations. Methods This was a cross-sectional retrospective study assessing the dose adequacy of drug treatment of 400 cirrhotic patients at hospital admission based on the authors' own previous studies and standard literature. The prevalence of total and preventable ADRs and of hospitalizations due to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
63
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 20 publications
1
63
0
3
Order By: Relevance
“…In patients with liver cirrhosis, the bioavailability of such drugs can reach 100% due to intra- and extrahepatic porto-systemic shunts [1], [5], [6]. High-extraction drugs must therefore be dosed very carefully in this population to avoid dose-dependent adverse reactions [7].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with liver cirrhosis, the bioavailability of such drugs can reach 100% due to intra- and extrahepatic porto-systemic shunts [1], [5], [6]. High-extraction drugs must therefore be dosed very carefully in this population to avoid dose-dependent adverse reactions [7].…”
Section: Introductionmentioning
confidence: 99%
“…Loop diuretics (furosemide and torsemide) and potassium-sparing diuretics (spironolactone) are the most widely used drugs (59 % on admission) in cirrhotic patients with ascites [8]. They are also the class of drugs most frequently associated with an adverse drug reaction such as metabolic disorder (hyperkalemia or hyponatremia) or worsening renal function [9].…”
mentioning
confidence: 99%
“…The authors also lamented that, by adding a label of exercising COMMENTARIES caution for use in patients with liver disease, the "problem is shifted to the prescriber." 12 In summary, a large number of widely prescribed drugs carry liver disease-related labeling in their official package inserts, and there is substantial discrepancy in the labeling by US and European agencies. It would be important for the regulatory authorities and Pharma to reevaluate the process by which package inserts are developed and consider a universal package insert wherever feasible.…”
Section: Commentariesmentioning
confidence: 99%
“…11 The same group of researchers also found that 20% of drug prescriptions to patients with cirrhosis were inappropriate, mostly owing to inaccurate doses or prescribing otherwise contraindicated drugs. 12 Patients with inadequately dosed drugs were more frequently hospitalized owing to adverse drug reactions. 12 As the authors pointed out, in contrast with impaired renal function, no generally accepted dose recommendations exist for patients with impaired liver function.…”
Section: Commentariesmentioning
confidence: 99%
See 1 more Smart Citation